2017
DOI: 10.1016/j.carpath.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

A novel role for the Krüppel-like factor 14 on macrophage inflammatory response and atherosclerosis development

Abstract: Genome-wide association studies have shown that Krüppel-like factor 14 (KLF14) is associated with both Type 2 diabetes mellitus and lipid metabolism. However, its role in chronic inflammatory responses and the pathogenesis of atherosclerosis remains unknown. The present study was designed to investigate both in vivo and in vitro the impact of KLF14 on chronic inflammatory responses and atherosclerosis. ApoE KO mice, a well-established animal model of atherosclerosis, had higher expressions of KLF14 in aorta ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…The observed hypermethylation of KLF14 also indicates accelerated aging of elite athletes. Recent findings showing the role of KLF14 in chronic inflammatory responses and the pathogenesis of atherosclerosis may be particularly relevant to this finding [ 40 , 41 ]. Wei et al showed that KLF14 may be involved in induction of inflammation and for this reason knockdown of this gene reduces pro-inflammatory cytokines and the formation of atherosclerotic lesions.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The observed hypermethylation of KLF14 also indicates accelerated aging of elite athletes. Recent findings showing the role of KLF14 in chronic inflammatory responses and the pathogenesis of atherosclerosis may be particularly relevant to this finding [ 40 , 41 ]. Wei et al showed that KLF14 may be involved in induction of inflammation and for this reason knockdown of this gene reduces pro-inflammatory cytokines and the formation of atherosclerotic lesions.…”
Section: Discussionmentioning
confidence: 88%
“…Wei et al showed that KLF14 may be involved in induction of inflammation and for this reason knockdown of this gene reduces pro-inflammatory cytokines and the formation of atherosclerotic lesions. This anti-inflammatory effect was suggested to prevent atherosclerosis: a known chronic inflammatory disease [ 40 ]. It is interesting to speculate whether DNA methylation of TRIM59 is involved in the process of cellular senescence and the associated beneficial biological effects.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work by Wei and colleagues has begun to parse out details on how KLF14 contributes to atherogenesis. They found that Apoe − / − mice aortas had elevated levels of Klf14 on either high-fat diet or standard chow ( 115 ). This increase in Klf14 expression was associated with elevated pro-inflammatory cytokines in circulation: Klf14 adenoviral knockdown ameliorated this effect.…”
Section: Monocyte/macrophage Klfsmentioning
confidence: 99%
“…Importantly, overexpression of Klf14 in a macrophage cell line led to increased inflammatory cytokine production as well as total cholesterol and cholesteryl ester content, a classic signature of atherogenic foam cells ( 116 ). Mechanistically, KLF14-mediated inflammation seems to be dependent on p38 MAPK and ERK1/2 signaling leading to increased cytokine release ( 115 ). Together, this work provides evidence that KLF14 may play a causal role in modulating inflammation associated with atherosclerosis, further implicating it in metabolic disease.…”
Section: Monocyte/macrophage Klfsmentioning
confidence: 99%
“…The photothermal therapy has great potential in enhancing therapeutic efficacy and lowering adverse effects [5]. To date, several nanomaterials including Au-based nanocomposites [6][7][8][9], silver-based nanoparticles [10], palladium/silver nanosheets [11,12], carbon-based nanomaterials [13][14][15], and polymeric nanoparticles [16][17][18] have been developed for the treatment of cancer under (near-infrared) NIR laser irradiation. For example, Liu et al reported a novel TaOx@Cat hollow nanosphere as a bionanoreactor for effectively enhancing radiation therapy for cancer cells [19].…”
Section: Introductionmentioning
confidence: 99%